J. C. Bille Brahe: Kerteminde Værn. En Egns Land-forsvarsstyrker fra November 1943 til Januar 1976. (Kjerteminde Avis Forlag, 1985). 272 s., 159,- kr. - C. Willemoes Jørgensen, P. (Historie/Jyske Samlinger, 1987)
-